The coexistence of race and racism can they become extinct together? - Hutchinson, Janis Faye 1953- (Lanham, Md. University Press of America, 2005)
Race and racism are interconnected historically and in the modern world. This connection is related to changing social, political, and economic conditions that impact how we think of others and ourselves. Race and racism are also connected to biological discoveries that justified how we think of others and ourselves. The main focus of this book is the examination of these connections. It is argued that while both race and racism are social constructions, the justification for racism changed as the definition and attributes of races were modified to correspond new developments in biology and genetics.
Whereas biological discoveries are one side of this construction, changing social situations represent the other side. That is, racism also responds to changing social, political, and economic conditions that alter its justification. In addition, scientific constructions of race were impacted by social factors that served to direct the "scientific disclosures" on human diversity. These factors form the context for the intricate relationship between race and racism.
Chapter 1 Race and Racism--Chapter 2 Early Prejudices--Chapter 3 Race, Racism and Slavery in the United States--Chapter 4 Race, Racism, and Science I--Chapter 5 Race, Racism, and Science II--Chapter 6 Race, Racism, and Health in America--Chapter 7 Scientific Statements on Race--Chapter 8 Race, Racial Identities, and Racism Today.
Includes bibliographical references (pages [165]-184) and index.
Tac-3521g donated by Dr. Rogelia Pe-Pua on 29 October 2021.
Keywords: Race; Racism; Race relations